Diphenolic acid-modified PAMAM/chlorinated butyl rubber nanocomposites with superior mechanical, damping, and self-healing properties. Issue 1 (31st December 2021) - Lu, Yao; Wang, Jincheng; Wang, Le; Song, Shiqiang
ABSTRACT: Based on its excellent damping properties, traditional rubber has been widely used in various industries, including aerospace, rail transit and automotive. However, the disadvantages of effective damping area, unstable damping performance, easy fatigue, and aging, greatly limited the further application of rubber materials. Thus, it is important to develop novel modified rubber damping materials. Herein, polyamidoamine dendrimers with terminal-modified phenolic hydroxyl and amine groups (G2 PAMAM-H) were designed and used as modifiers to improve the damping performance of chlorinated butyl rubber (CIIR). The results showed that the modification of G2 PAMAM by diphenolic acid can avoid its aggregation in the CIIR matrix. CIIR/G2 PAMAM-H nanocomposites exhibited high tan δ max of 1.52 and wide damping temperature region of 140°C (tan δ  > 0.55)at a very low loading (4.32 wt.%), which were strongerthan that of pure CIIR and CIIR/G2 PAMAM nanocomposites. In addition, these nanocomposites also exhibited a unique self-healing ability by multiple hydrogen bonds, which can effectively extend the life of the rubber material in actual production. Therefore, the dendrimer modification provided unique development opportunities for elastomers in certain highly engineered fields, such as vehicles, rail transit, aerospace, etc. GRAPHICAL ABSTRACT: uf0001